Overview of Self-Regulation for Santri in Memorizing the Qur'an at Home: Gambaran Regulasi Diri pada Santri dalam Menghafal Al Qur’an di Rumah - Azizah, Adnes Nur; Affandi, Ghozali Rusyid (Psikologia : Jurnal Psikologi, 2023)
Obstacles in seeing in the process of memorizing the Qur'an and the hectic schedule at Rumah Qur'an Ar Rahman requires both subjects to have good self-regulation in order to achieve their goal of becoming a memorizer of the Qur'an. This study aims to describe the self-regulation of Tahfidzul Qur'an Low vision students in memorizing the Qur'an at the Qur'an Ar Rahman House. This study uses a phenomenological qualitative research method, with a sample of 2 subjects with Low vision who undergo the process of memorizing the Qur'an, the sampling technique of this study uses purposive sampling. The data collection technique used by the researcher is interviews. . The results of this study state that Tahfidzul Qur'an students who have Low vision have self-regulation abilities, one of which is marked by a metacognitive process in the process of memorizing the Qur'an and balancing between memorizing and repeating memorization activities as well as school activities and additional activities at Rumah Qur'an. 'an Ar Rahman.